Effect of air-particle abrasion and methacryloyloxydecyl phosphate primer on fracture load of thin zirconia crowns: an in vitro study - Ruwaida Z. Alshali; Mohammed A. Alqahtani; Basem N. Alturki; Loay I. Algizani; Abdullah O. Batarfi; Zuhair K. Alshamrani; Razan M. Faden; Dalea M. Bukhary; Mosa M. Altassan (Frontiers Media S.A., 2024)
The study aimed to investigate the effects of airborne-particle abrasion (APA) and 10-methacryloxydecyl dihydrogen phosphate (10-MDP primer) surface treatments on the fracture load of thin zirconia crowns made from 3Y-TZP and 5Y-PSZ zirconia. Eighty full-contour zirconia crowns of 0.5 mm thickness were fabricated from 3Y-TZP and 5Y-PSZ zirconia. Crowns of each material were divided into four groups based on the surface treatment applied to the fitting surface (n = 10): Group 1 (control), Group 2 (10-MDP Primer Only), Group 3 (APA Only), and Group 4 (10-MDP Primer + APA). Crowns were cemented using self-adhesive resin cement and subjected to thermocycling. Fracture load tests were performed using a universal testing machine with a hemispherical indenter. Statistical analysis was performed using one-way ANOVA, Tukey's post hoc test, and independent samples T-test (α = 0.05). The fracture load of 3Y-TZP was significantly higher than 5Y-PSZ crowns across all groups (P ≤ 0.001). Group 1 had the lowest fracture load, while Group 4 had the highest for both materials. In 3Y-TZP, the fracture load of Group 2 increased by 40% (P = 0.002) and Group 3 by 50% (P < 0.001) compared to Group 1. Group 4 showed a 90% increase over Group 1 (P < 0.001). For 5Y-PSZ, fracture load of Group 4 increased by 70% compared to Group 1 (P < 0.001). It was concluded that applying a 10-MDP primer or APA significantly increases the fracture load of thin 3Y-TZP zirconia crowns, with the combination of both treatments yielding the highest values. For 5Y-PSZ, a significant increase in fracture load is observed only when both APA and the 10-MDP primer are used together.